Penal Policy Dilemma: Child Drug Couriers in Indonesia’s Juvenile Justice System - Novieyan Yahya; Putri Haliza Yuniar; Kadi Sukarna; Zaenal Arifin (Journal of Law Justice (JLJ), 2026)
This study aims to analyze the role and patterns of adolescent involvement as drug couriers in Sumbawa Barat Regency, identify the factors influencing adolescents' vulnerability within drug trafficking networks, and assess the effectiveness of law enforcement and prevention strategies implemented from the perspective of child protection and the juvenile justice system. The method of research used is a qualitative approach with a case study strategy thru in-depth interviews with law enforcement officers, field observations, and the study of official documents related to narcotics cases involving adolescents. The novelty of this research lies in its specific focus on examining the position of adolescents as drug couriers in the Sumbawa Barat Regency, which has been minimally studied in the literature on juvenile criminal law in Indonesia. The study's results indicate that law enforcement against juvenile drug couriers still faces various obstacles, including legal procedures that are not yet fully child-friendly, weak rehabilitative orientation, and lack of coordination between law enforcement agencies and rehabilitation institutions. This study concludes that there is a need to strengthen the capacity of law enforcement officers, optimize rehabilitation programs, and consistently apply preventive and restorative approaches so that the handling of drug cases involving adolescents is not only repressive but also capable of sustainably reducing the involvement of adolescents in drug trafficking.